Determination of the most potent precursors of advanced glycation end products (AGEs) in chips, crackers, and breakfast cereals by high performance liquid chromatography (HPLC) using precolumn derivatization with 4-nitro-1,2-phenlenediamine - Cengiz, Serdar; Kismiroglu, Cemalettin; Cebi, Nur; Catak, Jale; Yaman, Mustafa (ELSEVIER, 2020)
Consumption of processed foods is increasing in today's modern diet. Advanced glycation end products (AGEs) can be formed by Maillard reactions as well as oxidation of proteins and fats in food processing. The aim of the present study was to determine the amount of glyoxal and methylglyoxal in chips, crackers, and breakfast cereals and to evaluate their effects on human health. In this research, chips (26), crackers (5), and breakfast cereals (11) were obtained from different markets in Istanbul, Turkey. The amounts of glyoxal and methylglyoxal in these foods were determined by high performance liquid chromatography (HPLC) using 4-nitro-1,2-phenlenediamine as a pre-column derivatizing reagent. The measured amount of glyoxal and methylglyoxal ranged between 94 and 1464 and 123-661 mu g/100 g in chips, and between 338 and 1936 and 727-1397 mu g/100 g in crackers, and between 8 and 1575 and 111-1201 mu g/100 g in breakfast cereals, respectively. The products used in this study, especially chips and crackers, contained high fat and were baked at a high cooking temperature. Therefore, these products had higher amounts of AGE precursors. Besides, high salt content in crackers may affect the increased amount of glyoxal and methylglyoxal. On the contrary, low fat containing breakfast cereals had lower amounts of AGE precursors. People who often consume AGE-rich snack foods will be at higher health risk than those who consume less. The health problems associated with AGEs can be reduced with an AGE-restricted diet.
Keywords: AGEs; Glyoxal; Methylglyoxal; Snack Foods; Breakfast cereals; HPLC; ALPHA-DICARBONYL COMPOUNDS; FOODS; ACRYLAMIDE; GLYCOXIDATION; GREEN; Chemistry